Zagotavljanje in naročanje zasebne varnosti v Republiki Sloveniji - Dvojmoč, Miha (2019)
Providing and ordering private security in the Republic of Slovenia. The guidelines in the form of a manual include knowledge of a broader field of security such as private security, corporate security and public procurement law. The publication directs the subscribers to the easier and more correct selection of the provider of private security services, based on the analysis of the regulation of the field of private security in as many as 32 European countries, the analysis of the characteristics of the operation of private security in Slovenia and the analysis of public procurement in Slovenia. Among other things, the manual emphasizes the importance of the quality of the private security services, the criteria for the selection of the provider and the appropriate ratio between the quality and the price of the services provided on the market. The possible criteria for ordering or selecting private security services for different sectors (trade, public administration, industry, financial sector and natural persons - house security) are included, which are specific to the Slovenian situation and are a cross section of theoretical thinking and suggestions and experience of experts from the economic activities to which they relate.
Keywords: private security; procurement; subscribers; bidders; procurement criteria